2022
DOI: 10.1101/2022.12.01.518705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AUTS2 gene dosage affects synaptic AMPA receptors via a local dendritic spine AUTS2-TTC3-AKT-mTORC1 signaling dysfunction

Abstract: The Human 1.2-MbAUTS2locus on chromosome 7q11.22 encodes a 1259-aa full-length protein, and a 711-aa C-terminal isoform. Functions of these AUTS2 proteins are only partly known. The major traits found in patients displaying AUTS2 locus mutations are Intellectual Disabilities, microcephaly attention deficit hyperactivity disorder (ADHD) (54%), and autistic traits. Furthermore,AUTS2common variants were recently found associated to alcohol consumption and dyslexia using GWAS approaches. Auts2 localizes mainly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We recently demonstrated that AUTS2 directly interacts with TTC3 a E3 ligase of AKT that regulates dendritic spine function via mTORC1-dependent local translation 45 (Fig. 6E).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We recently demonstrated that AUTS2 directly interacts with TTC3 a E3 ligase of AKT that regulates dendritic spine function via mTORC1-dependent local translation 45 (Fig. 6E).…”
Section: Resultsmentioning
confidence: 95%
“…The third type of Auts2 mouse model developed by our group 45 is based on either deletion or duplication of the ~1.2 Mb Auts2 locus. We evidenced repetitive and restricted behaviors (rearing) in Del/+ mice.…”
Section: Discussionmentioning
confidence: 99%